Safety and efficacy of an essential oil from Elettaria cardamomum (L.) Maton when used as a sensory additive in feed for all animal species. (6th June 2019) - ; Bampidis, Vasileios; Azimonti, Giovanna; de Lourdes Bastos, Maria; Christensen, Henrik; Kouba, Maryline; Kos Durjava, Mojca; López‐Alonso, Marta; López Puente, Secundino; Marcon, Francesca; Mayo, Baltasar; Pechová, Alena; et al.
Abstract: Following a request from the European Commission, the EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the safety and efficacy of an essential oil from the seeds of Elettaria cardamomum (L.) Maton when used as a sensory additive for all animal species. Characterisation of the essential oil identified 37 components accounting for > 99% of its composition, with terpineol acetate (> 35%) and 1, 8‐cineole (> 20%) being the most prevalent compounds. In the absence of toxicological data of the feed additive itself, a component‐based approach was applied to assess the safety of the essential oil as a mixture. Based on structural and metabolic similarity, the components of cardamom oil were allocated to seven assessment groups. Assuming the absence of toxicologically relevant interactions among components, dose addition was applied within each assessment group by calculating the combined margin of exposure as a basis for risk characterisation. The FEEDAP Panel concluded that the additive under assessment is safe at the proposed use level of 5 mg/kg in feed for all animal species. A concentration of 5 mg/L water for drinking is considered safe for all animal species. The use of cardamom essential oil in animal feed is considered safe for the consumer. In the absence of studies, the Panel cannot conclude on the safety for the users when handling the additive. The use of the essential oil under assessment in animal production is not expected to pose a risk for the environment. Since the seeds of E. cardamomum and their preparations are recognised to flavour food and their function in feed would be essentially the same, no further demonstration of efficacy is considered necessary. The Panel made a recommendation to limit the content of methyleugenol in the oil.